Does fair play reduce concussions? A prospective, comparative analysis of competitive youth hockey tournaments. Issue 1 (4th March 2016) - Smith, Aynsley M; Gaz, Daniel V; Larson, Dirk; Jorgensen, Janelle K; Eickhoff, Chad; Krause, David A; Fenske, Brooke M; Aney, Katie; Hansen, Ashley A; Nanos, Stephanie M; Stuart, Michael J
Abstract : Background/aim: To determine if Boys Bantam and Peewee and Girls U14 sustain fewer concussions, head hits, 'other injuries' and penalties in hockey tournaments governed by intensified fair play (IFP) than non-intensified fair play (NIFP). Methods: A prospective comparison of IFP, a behaviour modification programme that promotes sportsmanship, versus control (non-intensified, NIFP) effects on numbers of diagnosed concussions, head hits without diagnosed concussion (HHWDC), 'other injuries', number of penalties and fair play points (FPPs). 1514 players, ages 11–14 years, in 6 IFP (N=950) and 5 NIFP (N=564) tournaments were studied. Results: Two diagnosed concussions, four HHWDC, and six 'other injuries' occurred in IFP tournaments compared to one concussion, eight HHWDC and five 'other injuries' in NIFP. There were significantly fewer HHWDC in IFP than NIFP (p=0.018). However, diagnosed concussions, 'other injuries', penalties and FPPs did not differ significantly between conditions. In IFP, a minority of teams forfeited the majority of FPPs. Most diagnosed concussions, HHWDC, and other injuries occurred to Bantam B players and usually in penalised teams that forfeited their FPPs. Conclusions: In response to significant differences in HHWDC between IFP and NIFP tournaments, the following considerations are encouraged: mandatory implementation of fair play in regular season and tournaments, empowering tournament directors to not accept heavily penalised teams, and introducing 'no body checking' in Bantam.